Visiting Nurses' Perspectives on Practices to Achieve End-of-Life Cancer Patients' Wishes for Death at Home: A Qualitative Study - Noriko Teruya; Yoko Sunagawa; Haru Sunagawa; Takehiko Toyosato (Elsevier, 2019)
Objective: This study aimed to clarify visiting nurses' perspectives on critical practices to ensure they could advocate for patients who prefer to die at home. Methods: Sixteen nurses, working at home-visit nursing agencies in Japan, participated in this study. Data were generated by interviews with the nurses and participant observations from nursing home-visits for six end-of-life cancer patients and were analyzed using content analysis. Results: Five themes emerged: (1) nursing assessment, (2) support for comfortable daily life of the patient and their family, (3) advocating for the patient's views about continuing homecare until death, (4) supporting the patient's preparedness for death, and (5) coordination with other health professionals and related facilities for a comfortable environment for the patient. In addition, the nurses sometimes used humorous responses to death-related work to change the patient's melancholy thoughts. Conclusion: The present study found that the participants advocated for the patient's views about continuing homecare until death while coordinating views between the patient and their family; they further supported the patient's daily life while helping them prepare for death to achieve their wish for death at home. In addition, our study uncovered the visiting nurses' unconscious practical wisdom of using humorous responses to death-related work to alleviate the patients' feelings of hopelessness. To develop practical wisdom for using humor effectively in end-of-life care, nurses need to verbalize unconscious practices, and accumulate empirical knowledge about nursing interventions using humor, including cultural attitudes, through case study analysis.